The mechanical properties of LDPE composite filled with CF coated by dimethylamine treated TiO2 - Jian, Li (Surface and interface analysis, 2022)
In order to improve the surface wettability of carbon fiber and enhance its composite interface performance, dimethylamine treated TiO2 was coated on carbon fiber (CF). The surface morphology, surface chemical state, and surface wettability of CF were characterized by SEM, XPS, and TEM tests, and the interlaminar shear strength (ILSS) and cross‐sectional morphology tests were used to test the performance of CF/Low density polyethylene (LDPE) composites. The interface bonding status was analyzed and characterized. The results show that after the surface treatment of CF by dimethylamine treated TiO2, the O/C (atomic ratio) of the surface of CF is increased, and a certain amount of nano‐scale small convex micro‐mechanical structure is given, which improves the surface wetting of CF. The surface of the CF modified by the TiO2 is rough; the contact area between modified CF and LDPE increases.